Peran Human Capital dalam Efektifitas Strategi Inovasi pada Era Teknologi - Sunarto Sunarto; Ratih Pratiwi (Jurnal Iqtisad, 2022)
AbstractThe development of quality human resources is essentially aimed at improving intellectual abilities, so that higher productivity can be achieved. HR and innovation should be viewed as closely related concepts, which together create a reinforcing cycle of value creation. Since HR is one of the main sources of innovation, the innovation strategy needs to include various relevant initiatives to stimulate HR. This is an important key as a new force in achieving economic prosperity in the era of competition in science and technology. Strategic planning is needed in order to adjust internal strengths so that they are always ready to seize opportunities and overcome external threats if you want to maintain a competitive advantage. So this article aims to identify the relevant gaps in human resources related to innovation performance, in order to create a more effective innovation strategy. The proposed approach, linking HR with an innovation strategy using gaps in HR for a more comprehensive assessment of innovation performance, enables countries/regions/cities/ organizations to create adequate innovation strategies/policies in the knowledge age.Keywords: Human Capital; innovation; effective strategies. AbstrakPengembangan sumber daya manusia yang berkualitas pada hakekatnya ditujukan untuk meningkatkan kemampuan intelektual, sehingga dapat dicapai produktivitas yang lebih tinggi. SDM dan inovasi harus dipandang sebagai konsep yang terkait erat, yang bersama-sama menciptakan memperkuat lingkaran penciptaan nilai. Karena SDM adalah salah satu sumber utama inovasi, strategi inovasi perlu mencakup berbagai inisiatif yang relevan untuk merangsang SDM. Hal ini menjadi kunci penting sebagai kekuatan baru dalam mencapai kesejahteraan ekonomi di era persaingan ilmu pengetahuan dan teknologi. Perencanaan strategis diperlukan dalam rangka menyesuaikan kekuatan internal agar selalu siap menangkap peluang dan mengatasi ancaman dari luar jika ingin mempertahankan keunggulan bersaing. Maka artikel ini bertujuan untuk mengidentifikasi kesenjangan yang relevan dalam sumber daya manusia terkait dengan kinerja inovasi, untuk menciptakan strategi inovasi yang lebih efektif. Pendekatan yang diusulkan, yang menghubungkan SDM dengan strategi inovasi yang menggunakan celah di SDM untuk penilaian kinerja inovasi yang lebih komprehensif, memungkinkan negara/wilayah/kota/ organisasi untuk menciptakan strategi/kebijakan inovasi yang memadai di era pengetahuan.